2013
DOI: 10.1371/journal.pone.0062995
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Analysis of Flight Behavior of Anopheles gambiae sensu stricto Malaria Mosquitoes in Response to Human Odor and Heat

Abstract: Female mosquitoes use odor and heat as cues to navigate to a suitable landing site on their blood host. The way these cues affect flight behavior and modulate anemotactic responses, however, is poorly understood. We studied in-flight behavioral responses of females of the nocturnal malaria mosquito Anopheles gambiae sensu stricto to human odor and heat. Flight-path characteristics in a wind tunnel (flow 20 cm/s) were quantified in three dimensions. With wind as the only stimulus (control), short and close to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
122
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(135 citation statements)
references
References 41 publications
(50 reference statements)
12
122
1
Order By: Relevance
“…50 The wind tunnel assay is more sensitive to reveal behavioral effects than the current WHO assays and could be considered as an additional method useful for investigating spatial repellent effects of current and new insecticidal compounds. 51 In the wind tunnel setup, in the presence of human host cues, it was found that both susceptible and resistant An.…”
Section: Discussionmentioning
confidence: 99%
“…50 The wind tunnel assay is more sensitive to reveal behavioral effects than the current WHO assays and could be considered as an additional method useful for investigating spatial repellent effects of current and new insecticidal compounds. 51 In the wind tunnel setup, in the presence of human host cues, it was found that both susceptible and resistant An.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental contexts where conditions cannot be reliably controlled (such as imaging of mosquitoes in their natural habitats), more complex algorithms for object definition and tracking, or indeed the use of 3D imagery, may be necessary to obtain meaningful data (Beeuwkes et al, 2008;Spitzen et al, 2013;Wu et al, 2009).…”
Section: Analyzing Nycthemeral Flight Activity Of a Albopictus Malesmentioning
confidence: 99%
“…Single camera setups are a suitable solution, however they are unable to record the depth of observed objects, and therefore tracks are recorded in two dimensions (2D). For this reason dual or multi-camera setups are increasingly employed for the observation of insect flight, which permits the reconstruction of 3D tracks from multiple views of the insects (Beeuwkes et al, 2008;Butail et al, 2012;Spitzen et al, 2013). Although multicamera techniques remain essential for a complete description and analysis of complex individual interactions (El-Sayed et al, 2000;Khan et al, 2005;Wu et al, 2009), they have a number of drawbacks: they are prohibitively expensive for many laboratories, require precise imaging calibration for their correct installation, and use relatively complex and computationally demanding techniques for 3D position reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, commercial software also had limitations regarding the computers suitable to run the programs and were useable on a limited number of operating systems (e.g. ; Observer XT, Noldus 2015;INTERACT, Mangold 2015), while usually offering a powerful set of analytical features (Adamson et al 2013;Spitzen et al 2013).…”
Section: Introductionmentioning
confidence: 99%